The Effect of The Process oriented Guided Inquiry Learning (Pogil) Learning Model on Social Literacy Abilities - Nur Fadhilah, Mutik; Nurahman, Mohamad; Septiana, Nanda; Nisak, Kamilatun (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
This study aims to investigate the effect of the Process Oriented Guided Inquiry Learning (POGIL) model on students' social literacy abilities. The background of this research is the increasing need for students to develop social literacy skills, which encompass critical thinking, communication, empathy, and active participation in societal issues. Traditional teaching methods often fail to foster these skills, thus hindering students' ability to engage with social challenges. POGIL, an inquiry-based learning model, emphasizes active student participation and collaboration, making it a promising approach for enhancing social literacy. This research employed a pre-experimental design with a one-group pretest-posttest design to evaluate the effectiveness of POGIL in improving social literacy. The sample consisted of second-grade elementary school students. Data were collected through pretest and posttest assessments, along with observational checklists. The results indicated a significant improvement in students' social literacy abilities after the implementation of POGIL. The average score of social literacy increased from 36.3% in the pretest to 86.8% in the posttest. This suggests that the POGIL model is effective in enhancing students' understanding of social issues, their ability to empathize, collaborate, and communicate effectively in social contexts.